Implementasi Teknik Reading Aloud dalam Meningkatkan Kemampuan Membaca Al-Qur’ān Surah Pendek pada Siswa Kelas V Di Madrasah Ibtidaiyah Negeri 2 Sambas Tahun Pelajaran 2019-2020 - Syaifudin Udin; Wildawati Wildawati; Nuraini Nuraini (Sekolah Tinggi Agama Islam Taruna Surabaya, 2021)
The purpose of this study was to reveal: 1) The steps of aloud reading techniques in improving the ability to read the short al-Qur'ān surah in grade V students at Madrasah Ibtidaiyah Negeri 2 Sambas in the 2019-2020 school year; 2) The results of the implementation of the aloud reading technique in improving the ability to read the short al-Qur'ān surah in grade V students at Madrasah Ibtidaiyah Negeri 2 Sambas in the 2019-2020 academic year. This research uses a qualitative approach and descriptive research type. Data collection techniques using interviews, observation and documentation. The data analysis technique used is data reduction, data display and conclusions. The results showed that; 1) The steps for implementing the aloud reading technique in improving the ability to read the short al-Qur'ān surah in grade V students at Madrasah Ibtidaiyah Negeri 2 Sambas for the 2019-2020 academic year, namely: a) The teacher chooses a short surah to read aloud; b) The teacher distributes al-Qur'ān Hadith textbooks to students; c) The teacher asks students to read a short surah together; d) When the reading is in progress, the teacher stops the students' reading in several places. Then the teacher pointed out and asked questions regarding the law of reciting recitation. The teacher gives sufficient time to discuss the students; e) The teacher divides students into groups and reads the surah in turn; f) The teacher ends the learning process by giving questions and conclusions. 2) The results of the implementation of the aloud reading technique in improving the ability to read the al-Qur'ān short surah in grade V students at Madrasah Ibtidaiyah Negeri 2 Sambas in the 2019-2020 academic year is proven by the results of the final test which show an increase in the reading ability of students with an average score 80, category